Cyber-Dilemmas: Gendered Hierarchies, New Technologies and Cyber-Safety in Schools - Shariff, Shaheen; Gouin, Rachel (Atlantis)

(untitled) (Mount Saint Vincent University, 2006)
This paper addresses gender issues relating to cyber-bullying among adolescents which is reflective of adult Internet use. It highlights legal considerations to address the policy vacuum on this emerging form of gendered violence.